Functional Imaging of Hodgkin’s Disease with FDG-PET and Gallium-67 - Willkomm, Petra; Palmedo, H.; Grünwald, F.; Ruhlmann, J.; Biersack, H.-J. (Nuklearmedizin - NuclearMedicine, 1998)
We report a case of Hodgkin’s lymphoma (Stage I B) which was studied using Ga-67-scintigraphy as well as whole body FDG-PET. Ga-67-scintigraphy detected a slightly increased uptake in the paraaortic and pelvic lymph nodes. However, FDG-PET was able to localize a much larger number of affected foci with a high glucose utilization rate in the right and left paraaortal regions, in the middle of the epigastrium, in the right and left parailiacal regions and one focus in the left upper mediastinum. Our experiences give rise to the assumption that FDG-PET ist significantly superior to gallium scintigraphy in Hodgkin’s disease. Whole body FDG-PET can result in an upstaging of the patient and has therefore a major impact on the therapeutic management.
Keywords: Hodgkin’s lymphoma; FDG-PET; Ga-67-scintigraphy